2016
DOI: 10.1038/mi.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Gut dendritic cell activation links an altered colonic microbiome to mucosal and systemic T-cell activation in untreated HIV-1 infection

Abstract: HIV-1-associated disruption of intestinal homeostasis is a major factor contributing to chronic immune activation and inflammation. Dendritic cells (DCs) are crucial in maintaining intestinal homeostasis, but the impact of HIV-1 infection on intestinal DC number and function has not been extensively studied. We compared the frequency and activation/maturation status of colonic myeloid DC (mDC) subsets (CD1c+ and CD1cneg) and plasmacytoid DCs in untreated HIV-1-infected subjects with uninfected controls. Coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
210
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(230 citation statements)
references
References 55 publications
3
210
3
1
Order By: Relevance
“…Here the authors found that increased abundance of Prevotella in HIV-infected individuals was associated with increased mucosal T cell and dendritic cell (DC) activation [44]. Furthermore, the co-culturing of HAMBs with colonic lamina propria mononuclear cells, including Prevotella copri  and  Prevotella stercore, directly stimulated activation of CD1c+ DCs, compared to bacteria lost in HIV including Rumminococcus bromii [94**]. This may affect HIV pathogenesis given that the authors also demonstrated DC activation in mucosal tissues was associated with increased mucosal viral load, increased mucosal and systemic T cell activation, and increased plasma and mucosal cytokine production, including several cytokines associated with mortality in HIV infection IL-6, TNFα, IL-10, IL-1β, and IFNγ [94**].…”
Section: Microbial Dysbiosis In Immunity and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here the authors found that increased abundance of Prevotella in HIV-infected individuals was associated with increased mucosal T cell and dendritic cell (DC) activation [44]. Furthermore, the co-culturing of HAMBs with colonic lamina propria mononuclear cells, including Prevotella copri  and  Prevotella stercore, directly stimulated activation of CD1c+ DCs, compared to bacteria lost in HIV including Rumminococcus bromii [94**]. This may affect HIV pathogenesis given that the authors also demonstrated DC activation in mucosal tissues was associated with increased mucosal viral load, increased mucosal and systemic T cell activation, and increased plasma and mucosal cytokine production, including several cytokines associated with mortality in HIV infection IL-6, TNFα, IL-10, IL-1β, and IFNγ [94**].…”
Section: Microbial Dysbiosis In Immunity and Inflammationmentioning
confidence: 99%
“…Furthermore, the co-culturing of HAMBs with colonic lamina propria mononuclear cells, including Prevotella copri  and  Prevotella stercore, directly stimulated activation of CD1c+ DCs, compared to bacteria lost in HIV including Rumminococcus bromii [94**]. This may affect HIV pathogenesis given that the authors also demonstrated DC activation in mucosal tissues was associated with increased mucosal viral load, increased mucosal and systemic T cell activation, and increased plasma and mucosal cytokine production, including several cytokines associated with mortality in HIV infection IL-6, TNFα, IL-10, IL-1β, and IFNγ [94**]. Thus, there is a clear relationship between microbial dysbiosis on immunity and inflammation in HIV infection, and preventing or reversing this altered GI microbiome in HIV infection may result in beneficial effects on immunity.…”
Section: Microbial Dysbiosis In Immunity and Inflammationmentioning
confidence: 99%
“…Furthermore, the levels of several pathogenic Proteobacteria have been observed to increase during HIV infection, including those within the genera Campylobacter, Escherichia, Acinetobacter, Desulfovibrio, and Pseudomonas, as have those of Prevotella species (9)(10)(11). Indeed, these bacteria have been found to be more adherent to the epithelium, to be more prone to translocate, and to be drivers of inflammation in the context of HIV and SIV infections (8)(9)(10)14). In an effort to reverse the deleterious effects of gut dysbiosis, studies have been performed using probiotic microbes to improve health in HIV-infected individuals and using the SIVinfected macaque model.…”
mentioning
confidence: 99%
“…One mechanism underlying the increased mortality is dysfunction of the gastrointestinal (GI) tract, which is associated with inflammation during HIV infection. Several lines of evidence support the role of GI dysfunction in HIV-related disease, including (i) a consistent association between mortality in HIV-infected individuals and markers of microbial translocation and gut epithelial dysfunction (2-4), (ii) the association of microbial products that translocate during HIV or simian immunodeficiency virus (SIV) infection and inflammation (5)(6)(7), and (iii) dysbiosis of the gut microbiome during HIV infection, which results in inflammation (8)(9)(10).…”
mentioning
confidence: 99%
“…Drainage of microbial products to the liver may cause local inflammation, increased synthesis of triglycerides and fat droplet accumulation in hepatocytes, contributing to visceral adiposity [67, 68]. Additionally, both HIV infection and obesity are independently associated with gut microbiome alterations and increased intestinal permeability that further promote local and systemic inflammation [69-75]. Although a recent study demonstrated higher levels of monocyte activation and systemic inflammation in obese vs non-obese HIV-infected persons, additional research is needed to determine whether HIV and obesity have a synergistic effect on the burden of inflammation-related metabolic disease.…”
Section: Discussionmentioning
confidence: 99%